Optimizing Shopping Experience by Integrating Augmented Reality and Payment Gateway in SME Storefronts - Tju, Teja Endra Eng; Azaru, Nugraha Rama (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
In the rapidly evolving digital era, leveraging advanced technologies to enhance the online shopping experience has become crucial, especially for small and medium-sized enterprises (SMEs) aiming to compete in the global market. This research focuses on optimizing the shopping experience by integrating Augmented Reality (AR) and Payment Gateway technologies into a storefront platform specifically designed for women's clothing SMEs. The study begins with a comprehensive analysis of market trends, customer behavior, and the challenges faced by SMEs in adopting these technologies. A detailed literature review provides the foundation for developing a robust conceptual framework. The prototype development phase involves designing 3D models using CLO | 3D Fashion Design Software, converting these models into AR experiences with Meta Spark Studio, and integrating the Midtrans Payment Gateway using Laravel. The AR feature enables users to virtually try on clothes via Instagram, while the Payment Gateway ensures quick and secure transactions. The final phase involves rigorous functional and substantive testing, focusing on user experience, transaction efficiency, and overall system performance. Results demonstrate that the integrated prototype significantly enhances the shopping experience, providing seamless AR interactions and efficient payment processing. Users reported high satisfaction levels with the system's usability and security. The study concludes that integrating AR and Payment Gateway technologies into SME storefronts can substantially improve their competitiveness in the digital market, offering practical insights and guidelines for future implementations in the e-commerce sector.